2019
DOI: 10.1038/s41598-019-45866-w
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of defence and iron homeostasis genes in rice roots by the diazotrophic endophyte Herbaspirillum seropedicae

Abstract: Rice is staple food of nearly half the world’s population. Rice yields must therefore increase to feed ever larger populations. By colonising rice and other plants, Herbaspirillum spp. stimulate plant growth and productivity. However the molecular factors involved are largely unknown. To further explore this interaction, the transcription profiles of Nipponbare rice roots inoculated with Herbaspirillum seropedicae were determined by RNA-seq. Mapping the 104 million… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 121 publications
3
30
0
Order By: Relevance
“…This could be due to the fact that the inoculated plants were harvested at 7 dpi and therefore at an established state of the interaction between bacteria and rice. In contrast, previous studies revealed that the inoculation of beneficial rhizobacteria induced the regulation of at least 1,000 genes in rice roots at earlier time points after inoculation (Drogue et al, 2014; Brusamarello-Santos et al, 2019; Rekha et al, 2018). Moreover, compared with the only study that analyzed the leaf transcriptional response of rice to the inoculation by beneficial rhizobacteria that retrieved only 2,414 DEGs at early stages of the interaction (Wu et al, 2018), when our study identified data of at least 4,000 DEGs in leaves in response to both strains.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This could be due to the fact that the inoculated plants were harvested at 7 dpi and therefore at an established state of the interaction between bacteria and rice. In contrast, previous studies revealed that the inoculation of beneficial rhizobacteria induced the regulation of at least 1,000 genes in rice roots at earlier time points after inoculation (Drogue et al, 2014; Brusamarello-Santos et al, 2019; Rekha et al, 2018). Moreover, compared with the only study that analyzed the leaf transcriptional response of rice to the inoculation by beneficial rhizobacteria that retrieved only 2,414 DEGs at early stages of the interaction (Wu et al, 2018), when our study identified data of at least 4,000 DEGs in leaves in response to both strains.…”
Section: Discussionmentioning
confidence: 63%
“…Particularly, both bacterial strains induced the up-regulation of two genes encoding for ACO, which are enzymes implicated in the synthesis of ethylene (Ravanbakhsh et al, 2018). Interestingly, in response to the inoculation of other beneficial bacteria, genes coding for ACOs were down-regulated in rice roots (Drogue et al, 2014; Brusamarello-Santos et al, 2019). Also, important transcriptional regulations of ethylene responsive factors (ERFs) occur in response to both strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trichoderma asperellum-treated rice plants showed increased expression levels of genes involved in photosynthesis, cell wall, and ROS modulation systems (Doni et al, 2019). Another study showed that, upon infection by H. seropedicae, rice activated iron uptake for the promotion of iron homeostasis, and also stimulated the expression of bacterial genes involved in nitrogen fixation, cell motility, and cell wall synthesis; conversely, certain plant defense genes were repressed, which allowed the endophyte to enter and rapidly colonize the intercellular space and xylem (Brusamarello-Santos et al, 2019). Moreover, in barley, endophytic Serendipita vermifera led to an extension of the plant protection barrier via the specific induction of genes involved in detoxification and redox homeostasis (Sarkar et al, 2019).…”
Section: Colonization With Enhancement Of Abiotic Stressmentioning
confidence: 99%
“…The role of plant growth promoting bacteria in agriculture A survey of the literature establishes that many plant growth promoting bacteria (PGPB) can strongly influence plant growth and increase crop yields. Mechanisms have been suggested that support these actions, which include: antagonism toward phytopathogens and induction of plant resistance pathways [1]; phytostimulation through microbial production and secretion of plant relevant hormones like auxin, cytokinins, and gibberellins, as well as nitric oxide [2,3]; improvements in host nitrogen uptake via biological nitrogen fixation (BNF) [4]; and improvements in host micronutrient uptake [5,6].…”
Section: Introductionmentioning
confidence: 99%